A Critique of the jusnaturalist notion of marriage - a view from Italian legal practice - Prelevic Palladino, Aleksandra (Glasnik Advokatske komore Vojvodine, 2020)
This paper attempts to answer the following research question: What is modern marriage? I combine the critical analysis of the jusnaturalist view, more precisely the notion of marriage in the work of Robert George, with a conceptual analysis of marriage in the process of its transformation. In order to do this I examine the case of Italy, a society with a traditional, Catholic jusnaturalist conception of marriage, which enables testing the jusnaturalist view of marriage and pointing out what makes it dysfunctional in practice. Then, I examine how well-founded are the constituent components of the notion of "real marriage" both in the context of modern marriage and within George's conception of marriage itself. The paper’s central argument is that marriage is a legal institution in the process of redefining that involves an expansion of participants and a redistribution of hitherto known functions of marriage. It’s the author’s standpoint that there is a methodological possibility to functionally yet neutrally explain the nature of law, and so the institution of marriage. Thus I arrive at the new function of modern marriage and bring a value-neutral definition of modern marriage based on the idea of ​​a privileged emotional relationship.
Keywords: modern marriage, new function of marriage, privileged emotional relationship, jusnaturalism, concept of marriage, concept of marriage in Italy, real marriage, family and marriage, marriage as a value in itself, functional methodology, value neutrality